2009
DOI: 10.1002/cncr.24390
|View full text |Cite
|
Sign up to set email alerts
|

Tumor budding in tumor invasive front predicts prognosis and survival of patients with esophageal squamous cell carcinomas receiving neoadjuvant chemotherapy

Abstract: BACKGROUND:In neoadjuvant chemotherapy for advanced esophageal cancers, complete tumor regression has been difficult to achieve, and tumor often remained after chemotherapy. However, the best method for evaluating the response to chemotherapy based on histopathologic examination of residual tumors has not been established.METHODS:Studied were 74 patients who received neoadjuvant chemotherapy (5‐fluorouracil, cisplatin, and doxorubicin), followed by surgery for advanced esophageal squamous cell carcinoma. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
98
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(104 citation statements)
references
References 43 publications
6
98
0
Order By: Relevance
“…Our findings of tumor cell budding from focally disrupted prostate tumor capsule are consistent with those of a number of previous studies in human esophageal and colorectal cancers, which detected a similar pattern and frequency of tumor cell budding, and revealed that tumors with budding cells were significantly correlated with invasion, metastasis, and worse prognosis [39][40][41]. The results of our gene expression profiling are also in line with those of a recent study, which showed that microdissected cells from the periphery and the center of the same ductal carcinoma in situ had a markedly different frequency and pattern in the expression of 22 genes, assessed with Atlas human Cancer 1.2 Arrays containing 1176 known genes [42].…”
Section: Clinical Implications Of Tumor Cell Budding From Focally Dissupporting
confidence: 92%
“…Our findings of tumor cell budding from focally disrupted prostate tumor capsule are consistent with those of a number of previous studies in human esophageal and colorectal cancers, which detected a similar pattern and frequency of tumor cell budding, and revealed that tumors with budding cells were significantly correlated with invasion, metastasis, and worse prognosis [39][40][41]. The results of our gene expression profiling are also in line with those of a recent study, which showed that microdissected cells from the periphery and the center of the same ductal carcinoma in situ had a markedly different frequency and pattern in the expression of 22 genes, assessed with Atlas human Cancer 1.2 Arrays containing 1176 known genes [42].…”
Section: Clinical Implications Of Tumor Cell Budding From Focally Dissupporting
confidence: 92%
“…All patients received neoadjuvant chemotherapy, which consisted of 2 courses of 5-fluorouracil (5-FU), cisplatin, and Adriamycin, using the following protocol: Cisplatin was administered at 70 mg/m 2 , Adriamycin was administered at 35 mg/m 2 intravenously on day 1, and 5-FU was administered continuously from days 1 to 7 at 700 mg/m 2 /d. Two courses of chemotherapy were provided after an interval of 4 weeks (8). The median follow-up period was 22.4 months.…”
Section: Patients Treatment and Samplesmentioning
confidence: 99%
“…Neoadjuvant chemotherapy or chemoradiotherapy followed by surgery has emerged as a promising strategy for advanced esophageal cancer and in fact, good responders to such preoperative therapy show better survival (2,3). However, the reported response rate to cisplatin-based chemotherapy, which is widely used for esophageal cancer, is only modest, ranging from 25% to 48% (4-7) and nonresponders likely receive no survival benefit (8). The ability to predict the response to chemotherapy before treatment should limit the application of chemotherapy to selected patients who are likely to show some benefits, and allow tailoring such therapy to the individual patient with esophageal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Pre-operative chemotherapy administered at our hospital consisted of cisplatin, adriamycin and 5-fluorouracil (5-FU) (19). Cisplatin was administered at 70 mg/m 2 , adriamycin at 35 mg/m 2 by rapid intravenous infusion on Day 1; and 5-FU at 700 mg/m 2 administered by continuous intravenous infusion on Day 1-7.…”
Section: Patient Population From April 2000 To September 2008 385 Pmentioning
confidence: 99%
“…The extent of viable residual carcinoma at the primary site was assessed semi-quantitatively, based on the estimated percentage of viable residual carcinoma in relation to the macroscopically identifiable tumor bed that was evaluated histopathologically. The percentage of viable residual tumor cells within the entire cancerous tissue was assessed as follows: grade 3, no viable residual tumor cells; grade 2, <1/3 residual tumor cells; grade 1b, 1/3-2/3 residual tumor cells; grade 1a, >2/3 residual tumor cells; grade 0, no significant response to chemotherapy (19,20). The extent of residual carcinoma in regional lymph nodes was not assessed.…”
Section: Patient Population From April 2000 To September 2008 385 Pmentioning
confidence: 99%